Variability in functional traits mediates plant interactions along stress gradients. (24th April 2013) - Schöb, Christian; Armas, Cristina; Guler, Manuela; Prieto, Iván; Pugnaire, Francisco I.
Summary: Environmental gradients may influence a plant's physiological status and morphology, which in turn may affect plant–plant interactions. However, little is known about the relationship between environmental variation, physiological and morphological variability of plants and variation in the balance between competition and facilitation. Mountain ranges in dry environments have opposing altitudinal environmental gradients of temperature and aridity, which limit plant growth at high and low elevations. This makes them particularly suitable for exploring the relationships between environmental conditions, plant phenotype and plant–plant interactions. We hypothesized that different environmental stressors will differently affect the physiological status of a nurse plant. This, then, manifests itself as variation in nurse plant morphological traits, which in turn mediates plant–plant interactions by altering microhabitat conditions for the nurse and associated species. In an observational study, we measured a series of functional traits of Arenaria tetraquetra cushions as indicators of its physiological status (e.g. specific leaf area, relative water content) and morphology (e.g. cushion compactness, size). Measurements were taken along the entire elevation range where A. tetraquetra occurs. Furthermore, we analysed how these functional traits related to soil properties beneath cushions and the number of associated species and individuals compared with open areas. Cushions at high elevation showed good physiological status; they were compact and large, had higher soil water and organic matter content compared with open areas and showed the strongest facilitation effect of the whole elevation gradient – that is, the highest increase in species richness and abundance of beneficiaries compared with open areas. Physiological data at low elevation indicated stressful abiotic conditions for A. tetraquetra, which formed loose and small cushions. These cushions showed less improved soil conditions and had reduced facilitative effects compared with those at high elevation. Synthesis . Functional traits of the nurse species varied distinctively along the two opposing stress gradients, in parallel to the magnitude of differences in microenvironmental conditions between cushions and the surrounding open area, and also to the facilitation effect of cushions. Our data, therefore, provides a strong demonstration of the generally overlooked importance of a nurse plant's vigour and morphology for its facilitative effects. Abstract : This study demonstrates the generally overlooked importance of a nurse plant's vigor and morphology for its facilitative effects. Functional traits of the cushion plant Arenaria tetraquetra ssp. amabilis varied distinctively along two opposing stress gradients, in parallel to the magnitude of differences in micro‐environmental conditions between cushions and the surrounding open area, and also to the facilitation effect of cushions.